Role of Physical Education in the Process of Professional Musicians Training - Fakhrutdinova, Anastasia V.; Konovalov, Igor E.; Boltikov, Yuri V.; Fahrutdinova, Guzaliya Zh.; Eveleva, Anna D. (Journal of History Culture and Art Research, 2019)
The problem of physical education of college students is a fundamental step in the system of lifelong professional music education. The purpose of the article is to identify the organizational and pedagogical conditions for the implementation of the integration of physical education in the process of professional training of students of musical educational institutions. In the process of study, the following research we used: theoretical analysis and synthesis of scientific literature; the study and synthesis of advanced educational experience. At the same time, physical education is presented as an integrative component of improving the quality of professional training of musicians. It’s determined that the effective organizational conditions allowing the integration of physical education into the process of vocational training of students of musical secondary specialized colleges is the development of modern physical education, in which the structure and substantive accompaniment have a pronounced professional orientation. In turn, the pedagogical conditions allowing the integration processes are the level of physical culture teacher’s competence and the formation of students’ motivation to physical culture exercises.